Triathlon - Pyper, I.; Deakin, E.; Shaw, A. (Routledge handbook of strength and conditioning: Sport-specific programming for high performance, 2018)
As is clearly documented throughout this chapter, triathlon is a multi-faceted sport with many competing demands all combining to support the athletes` ability to develop, take part and compete at any level or distance of the sport. From a strength and conditioning perspective it is a mindset shift for a practitioner, where the importance of understanding the full training programme and the impact that this will have on the S&C delivery comes to the fore; this all-encompassing understanding is vital for athlete/coach buy-in and to deliver the best service possible. The strength and conditioning programme needs to be individualised as triathletes come from a variety of different sporting backgrounds, with many mechanical dysfunctions and imbalances. However, the broad programme principles apply to whomever the athlete is. The importance of lower limb and posterior chain strength is crucial for injury prevention but also for performance improvement. The ability to manage force and remain balanced and in control through the core to reduce energy leakages is fundamental, as is developing the work capacity and strength to allow the athlete to manage the training loads required to reach their full potential.